2019
DOI: 10.1111/wrr.12743
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory potential of Nisin A with application in wound healing

Abstract: Antimicrobial peptides can have a dual role with both antimicrobial activity against a broad range of bacteria and immunomodulatory effect, making them attractive as therapeutic treatment of difficult wounds. Nisin A is widely known for its antimicrobial activity, and a preliminary study demonstrated that it increased wound closure, but the mechanism behind its effect is unknown. The aim of this study is to elucidate the wound healing potential of Nisin A and the mechanism behind. First, an epithelial and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 47 publications
(92 reference statements)
2
16
0
1
Order By: Relevance
“…To date, nisin resistance has not been observed or reported in S. epidermidis strains. Alongside this, nisin A has also been found to promote wound healing, without any observable cytotoxic effects in mammalian cells when tested in animals [12,23,41]. This suggests that nisin A and other nisin derived peptides could be viable treatment options in the fight against and prevention of, medical device associated infections in the future.…”
Section: Discussionmentioning
confidence: 91%
“…To date, nisin resistance has not been observed or reported in S. epidermidis strains. Alongside this, nisin A has also been found to promote wound healing, without any observable cytotoxic effects in mammalian cells when tested in animals [12,23,41]. This suggests that nisin A and other nisin derived peptides could be viable treatment options in the fight against and prevention of, medical device associated infections in the future.…”
Section: Discussionmentioning
confidence: 91%
“…Mouritzen et al 38 evaluated in vitro and ex vivo wound healing potential of Nisin A using HaCaT, HUVEC cell lines and porcine skin and demonstrated that Nisin A can affect the process of wound healing by decreasing bacterial growth and modulating pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Nisin has been reported to have a significant antiinflammatory effect in vitro and in vivo. Nisin A can increase the activity of human keratinocytes HaCaT, inhibit LPSinduced proinflammatory cytokine levels (TNF-α), and reduce bacterial growth, promoting wound healing [73]. Nisin Z inhibits S. agalactiae and S. aureus and leads to a significantly decreased milk somatic cell count in cows with mastitis, thus effectively relieving the symptoms of mastitis [74].…”
Section: Anti-inflammation and Immunomodulation Activitiesmentioning
confidence: 99%